Prospective analysis of metabolic syndrome and inflammation in aortic aneurysm risk: UK Biobank study - Liu, Xinyi; Liu, Hao; Chen, Suwei; Gong, Chen; Ge, Yipeng; Qiao, Zhiyu; Li, Chengnan; Zhu, Junming (Frontiers in Endocrinology, 2025)
Context/ObjectivesMetabolic syndrome (MetS) is associated with various diseases, yet its connection with aortic aneurysm (AA) is not well understood. The role of chronic inflammation as a mediator in this relationship also remains unclear. This study explores the combined effects of MetS and inflammation on AA risk.MethodsData from 312,505 UK Biobank participants were analyzed to assess the relationship between MetS and AA. Cox proportional hazards regression models evaluated the association, while restricted cubic splines, mediation analyses, interaction assessments, and joint analyses explored the impact of inflammatory indicators, including the low-grade chronic inflammation (INFLA) score.ResultsOver a mean follow-up of 14.6 years, 2,382 participants developed AA. MetS was associated with a higher AA risk (HR: 1.27; 95% CI: 1.16–1.39) in fully adjusted models. Each additional MetS component increased AA risk by 16%. Inflammatory markers, including the INFLA score, significantly mediated this relationship. Joint analyses revealed a stronger association in MetS patients with high INFLA scores (HR: 1.68; 95% CI: 1.45–1.95).ConclusionMetS and its components notably elevate AA risk, with inflammation playing a key mediating role. These findings underscore the importance of targeted prevention strategies, particularly for MetS populations with high chronic inflammation.